Research Note: Floristic inventory of monocots in Mt. Pangasugan, Baybay, Leyte, Philippines - Abit, Pamela P. (Annals of Tropical Research, 2008)
Mt. Pangasugan which lies up to an elevation of 1,158 m ASL on the western slope of the Central Cordillera of Leyte is one of the unexplored mountains. Since directory of Philippine flora is still incomplete, a floristic inventory of the country’s remaining forest is imperative. The study was conducted to provide a checklist of existing monocot flora in Mt. Pangasugan. A total of 76 species belonging to 14 families and 51 genera were recorded. Family Araceae has the most number of genera while Family Palmae has the most number of species.